Teachers’ Tpack in Technology-Enhanced Writing Instruction: Evidence From EFL Classroms Using Grammarly - Setyowati, Yulis; Bhatti, Aisha (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2026)
The integration of digital technology into English as a Foreign Language instruction has become a crucial requirement in the Indonesian educational context. One technological tool that has recently gained prominence is Grammarly, an automated writing evaluation application that provides real-time feedback. However, the effectiveness of Grammarly in writing instruction largely depends on teachers’ Technological Pedagogical Content Knowledge (TPACK). This study aims to investigate how Indonesian EFL teachers demonstrate their TPACK of Grammarly in the writing course. Employing a qualitative case study design, data were collected through classroom observations, semi-structured interviews, and document analysis involving Indonesian EFL teachers. The findings demonstrate that teachers’ TPACK is enacted through three interrelated instructional practices in technology-enhanced writing instruction. Teachers shift traditional writing pedagogy toward technology-mediated learning by critically integrating Grammarly as a formative feedback tool rather than a corrective substitute. They further employ multimodal representations to scaffold students’ grammatical understanding within written discourse, while modeling effective writing practices through guided interpretation and selective uptake of Grammarly-generated feedback. The study critically concludes that strong TPACK is essential for preventing overreliance on automated feedback, enabling teachers to appropriate Grammarly as a pedagogically mediated resource that fosters students’ grammatical awareness, metalinguistic reflection, and autonomous writing development.